A BASIC OVERVIEW OF THE CHALLENGES IN TEACHING INTERCULTURAL COMMUNICATION AMONG TERTIARY LEVEL ENGLISH TEACHERS IN CHINA - Xuyiping Xuyiping; Norkhairi Ahmad; Salmah Anisah Abu Hasan (Universitas Duta Bangsa Surakarta, 2023)
This paper provides an overview and discussion on the current situation of intercultural communication training and challenges for tertiary English in China. A qualitative meta-analysis was conducted on research articles written both in Chinese language and English during the last two decades (from 2002) to explore reported challenges faced by teachers. Mitigating strategies undertaken were also scrutinized via documents analysis of the assorted papers. The findings showed that instructional efforts to develop intercultural communication competence in tertiary students was previously quite stagnant in its approaches, riddled with various micro and macro level challenges and quite unsuccessful in yielding the desired results. Only within the last decade with the advent of ICT and multimedia technology that concerted efforts could be integrated into producing considerable results. This study puts forth relevant improvement strategies derived from various aspects analyzed. They came in the form of inevitable measures like upgrading the teaching system, improving the quality of teachers, changing the teaching strategies, developing resource hub, developing professional teams and groupings, and optimizing intercultural communication evaluation mechanism. The findings from this study has high transferability andÂ insights for institutions in countries with similar contexts. It also provides beneficial theoretical reference for the training of intercultural communication competence in a foreign language learning context.